(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
This exhibition focuses on a brief analysis of psychological gender violence against women in the contemporary Brazilian legal system and aims to identify the treatment of the topic in current legislation, in the face of recent innovations. There is undeniable relevance in the discussion, since it is a woman’s right to live free from any violence or oppression, and acts contrary to this postulate manifestly violate their human rights, as prescribed by Law no. 11,340/06 (Maria da Penha Law). The present text is reasoned on research of a theoretical nature, developed through a review of correlated literature and analysis of legislation, associated with expository-argumentative technique, used for the critical discussion of the theme. In the end, it is concluded that laws nº 11.340/06, 14.132/21 and 14.188/21 constituted an important advance in the Brazilian legal system, in the repression of violence against women and in the safeguarding of their right to psychological integrity.